THE RELATIONSHIP BETWEEN GENDER AND THE LEVEL OF DEPRESSION AMONG STUDENTS IN INDONESIA: A CROSS-SECTIONAL STUDY - Irma Hanifatu Sa’adah; Rifka Pramudia Wardani; Yuniar Laksmi Eka Wardani; Wahyu Nur Aini; Jayanti Dian Eka Sari (Journal of Community Mental Health and Public Policy)
Background: College students are vulnerable to depression and anxiety, which are the main symptoms of mental emotional disorders that often occur today. Student depression can occur in female students or male students. The prevalence of mental illness characterized by symptoms and anxiety in the population aged 15 years and over is 6.1% of the total population. Purpose: The purpose of this study was to determine the relationship between gender and the incidence of depression in college students. Methods: This study used quantitative methods with data collection by incidental sampling on 54 (consisting of 36 women and 18 men) active students of the 6th semester of FIKKIA Universitas Airlangga Banyuwangi. Data collection was done online and analyzed using chi-square, using the CES-D instrument. Results: The results of the study found no relationship between gender and the level of depression in sixth semester students, with a value of ρ = 0.325 from the chi-square test, which shows there is no relationship between gender and depression.  Conclusion: In this study it showed no relationship was found between gender and levels of depression in students.